AN ANNOTATED TRANSLATION OF A MOTIVATION BOOK ENTITLED 7 KEAJAIBAN REZEKI - Robingah, Robingah; Suyudi, Ichwan (Universitas Gunadarma, 2014)
This is an annotated translation research. The problems of the research are: (1) What are the difficulties encountered by the researcher when translating a motivation book entitled 7 Keajaiban Rezeki into English? (2) How are those difficulties solved in the translation? The purposes of this research are: (1) To attain factual information concerning the problems faced by the translator/researcher in translating the source text. (2) To give plausible solutions to the difficulties encountered by the translator/researcher in translating the source text. The method used in this study is introspective and retrospective methods. Relevant translation strategies and theories are used in solving the problems that are encountered during the translation. Results obtained from this research show that there are 14 words, 6 phrases, 2 clauses, 1 pronoun, 1 idiom, and 1 sentence from 25 data analyzed that pose difficulty to be translated by the researcher/translator. Based on the 25 data which have been analyzed, it is found that there are 11 translation strategies employed by the researcher to solve the problems/difficulties in translating the source text into the target text, namely: 1 literal translation, 2 loans, 1 phrase structure change, 5 paraphrases, 1 clause structure change, 1 cohesion change, 1 abstraction change, 2 transpositions, 1 unit shift, 1 naturalization and 9 cultural filtering. Keywords: annotated translations, problems, solutions